2006
DOI: 10.1080/03602550500373741
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cu2+Ions from Aqueous Solutions by Starch-Graft-Acrylic Acid Hydrogels

Abstract: Gelatinized starch was prepared by constantly stirring a mixture of starch and water at 95 C for 1 hour. Starch-graft-acrylic acid (S-g-AA) hydrogels were prepared by grafting acrylic acid (AA) [monomer=starch (w=w) 0.5-1.5] onto gelatinized starch with ceric ammonium nitrate as initiator under nitrogen atmosphere. The surface morphology of samples was studied using a scanning electron microscope (SEM). The hydrogels were evaluated for the removal of Cu 2þ ion from aqueous solutions at different pH. The concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…As observed in Table 1, the amount of the G% of S-g-PMAA was found to be 43.6. When this result was compared with previous studies (Athawale and Lele, 1998;Athawale and Rathi, 1999;Aravindakshan and Kumar, 2002;Güçlü et al, 2006), it was observed that this product has a higher value of G% than those studies. In the previous study (Güler, 2011), when the non-gelatinized starch used in the grafting reaction, the amount of G% was found to be 30.9.…”
Section: Synthesismentioning
confidence: 37%
“…As observed in Table 1, the amount of the G% of S-g-PMAA was found to be 43.6. When this result was compared with previous studies (Athawale and Lele, 1998;Athawale and Rathi, 1999;Aravindakshan and Kumar, 2002;Güçlü et al, 2006), it was observed that this product has a higher value of G% than those studies. In the previous study (Güler, 2011), when the non-gelatinized starch used in the grafting reaction, the amount of G% was found to be 30.9.…”
Section: Synthesismentioning
confidence: 37%
“…In these preliminary studies, it was observed that Cu(II) ions collapsed at higher pH values than 6. In addition, Chg-IA and Ch-g-CA beads have negative charges (ionized form) at natural pH value (approximately 6) of metal ion solution [4]. Therefore, lower pH values than 6 are not suitable for adsorption studies because carboxyl groups of these beads are non-ionized form and, the optimal pH value was determined as "6" according to the preliminary adsorption studies, which were carried out at different pH values.…”
Section: Adsorption Studiesmentioning
confidence: 99%
“…Chitosan is obtained by deacetylation of chitin under alkaline conditions. Chitosan is a linear polysaccharide composed of glucosamine and N-acetyl glucosamine units linked by (1)(2)(3)(4) glycoside bonds. When the content of glucosamine (degree of deacetylation) of chitin is higher than about 50%, it is as named chitosan, and it becomes soluble in an aqueous acidic medium [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations